1998
DOI: 10.1161/01.str.29.12.2529
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis With Intravenous rtPA in a Series of 100 Cases of Acute Carotid Territory Stroke

Abstract: Background and Purpose-Although new, large, double-blind, randomized studies are needed to establish the efficiency of intravenous thrombolysis, open trials of sufficient size may also provide novel data concerning specific outcomes after thrombolysis. Methods-An open study of intravenous rtPA in 100 patients with internal carotid artery (ICA) territory strokes between 20 and 81 years of age, with a baseline Scandinavian Stroke Scale (SSS) score of Ͻ48 at entry was conducted. Inclusion time was within 7 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 50 publications
2
66
0
Order By: Relevance
“…2 Patients with internal carotid artery (ICA) occlusion are currently excluded from some thrombolytic trials 3 on the basis of potentially extensive infarction and lack of response to thrombolytic therapy. 4,5 However, it is unknown if all patients with ICA occlusion uniformly have extensive and homogenous infarcts and, if this is not the case, what modifies the extent and pattern of infarction. Researchers have examined the primary and ophthalmic collateral systems without success in explaining the difference in infarct extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Patients with internal carotid artery (ICA) occlusion are currently excluded from some thrombolytic trials 3 on the basis of potentially extensive infarction and lack of response to thrombolytic therapy. 4,5 However, it is unknown if all patients with ICA occlusion uniformly have extensive and homogenous infarcts and, if this is not the case, what modifies the extent and pattern of infarction. Researchers have examined the primary and ophthalmic collateral systems without success in explaining the difference in infarct extent.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, other investigators found that proximal ICA thrombosis conferred an odds ratio of 3.3 for a poorer outcome but also cautioned that only 30% of the patients had a good response to thrombolytic therapy. 4 It is possible that the patients with ICA occlusion who responded to thrombolytic therapy had recanalization of the MCA but that the therapy had no effect on recanalization of the ICA because of the larger thrombus burden. 16 …”
Section: Infarct Volume and Clinical Outcomementioning
confidence: 99%
“…Intravenous thrombolysis with a recombinant tissue plasminogen activator (t-PA), alteplase (Actilyse; Boehringer Ingelheim, Biberach, Germany), was given after MRI completion within the first seven hours after stroke onset according to a previously published protocol (11).…”
Section: Patient Protocolmentioning
confidence: 99%
“…Many studies have been published on the predictive value of factors like time-to-treatment [6][7][8][9] , severity of neurological deficits [10][11][12] and extension of early ischemic lesions on baseline CT scan on admission 11,13,14 , emphasizing how the best results can be obtained when rt-PA is administered within three hours of symptom onset in patients with an NIHSS score ≤ 25 and an ASPECT score > 7.…”
Section: Neuroradiologic Assessment and Identification Of Occlusion Sitementioning
confidence: 99%